Pandangan Hukum Islam Terhadap Keputusan Childfree dalam Perkawinan - Nazwa Safhira; Renita Dwi Norisma (INDO PUBLISHING, 2026)
This study investigates the childfree phenomenon within marital institutions by contrasting Islamic jurisprudence with Indonesian positive law. Employing a qualitative, juridical-normative approach through library research, the findings indicate that although traditional Islamic law prioritizes procreation (hifzh al-nasl), a mutual agreement to remain childfree can be understood via the reciprocity principle of mubadalah and the classical analogy of 'azl (contraception), provided it stems from rational justifications. Concurrently, Indonesian positive law does not explicitly forbid this practice, categorizing it under the legally protected domain of reproductive autonomy, provided it rests on uncoerced mutual consensus. The primary legal consequences intersect with inheritance law, which demands strategic asset mitigation using instruments like grants or wills. This study concludes that contemporary family resilience is determined by the stability of a couple's marital commitment rather than conventional reproductive success. Consequently, the adoption of prenuptial agreements serves as a vital preventive solution to guarantee legal certainty for couples navigating this modern lifestyle within an adaptive constitutional framework.